KONSEP PEMIKIRAN HARUN AR RASYID DALAM PENDIDIKAN KARAKTER DAN RELEVANSINYA PADA GENERASI Z - An Nahdliyah, Khumairoh; Purwanti, Ina (ILJ: Islamic Learning Journal, 2023)
The purpose of this study was to discuss the use of audio-visual media in improving learning skills in the Aqidah Akhlak course among MTs Miftahussalam students. An experimental research design with a control group was used in this study. The results showed that the use of audio-visual media improved students' learning skills in the topic of Akidah Akhlak in MTs Miftahussalam. The use of audio-visual media in learning as a successful and entertaining method for instructors and students is a recommendation that can be made. This research is expected to help establish new and effective learning strategies to improve the quality of learning for Akidah Akhlak courses in pesantren.